ANALISIS MOTIVASI BELAJAR MAHASISWA PENDIDIKAN BAHASA INGGRIS FKIP UNIVERSITAS LANCANG KUNING - Kurniawan Kurniawan (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2015)
Motivation in learning English is one of the big problems for someEnglish students in FKIP Lancang Kuning University. The aim of this researchis to find the range of English students’ motivation in learning English, intrinsicand extrinsic motivation of the students. This research is using interview andquestionare for 56 English students, and then analyzed by using SPSS to get thereal data and performs them in percentage, table, and diagram and thendescribed.